Thermokarst and precipitation drive changes in the area of lakes and ponds in the National Parks of northwestern Alaska, 1984–2018 - David K. Swanson (Arctic, Antarctic, and Alpine Research, 2019)
Lakes and ponds are important ecosystem components in arctic lowlands, and they are prone to rapid changes in surface area by thermokarst expansion and by sudden lake drainage. The 30 m resolution Landsat record (1984–2018) was used to derive a record of changes in the area of lakes and ponds in the five National Parks of northern Alaska. Surface-water area declined significantly in portions of the study area with ice-rich permafros t and water bodies of thermokarst origin. These declines were associated with rapid lake drainage events resulting from the thermoerosion of outlets. Thermoerosion was probably favored by the record warm mean annual temperatures in the study area, combined with precipitation that fluctuated near long-term normals. The rate of lake loss by rapid drainage was greatest in 2005–2007 and 2018. In landscapes with permafrost of lower ice content and water bodies in depressions of non-thermokarst origin, surface-water area generally fluctuated in response to year-to-year changes in precipitation, without a long-term trend, and lake drainage events were rare. Loss of surface water in ice-rich lowlands is likely to continue as the climate warms, with associated impacts on aquatic wildlife.